German bank lending to industrial and non-industrial countries: driven by fundamentals or different treatment? - Thorsten Nestmann (Deutsche Bundesbank, 2005)
This paper shows that the substantial disparity in German bank lending towards industrial (IC) and non-industrial (Non-IC) countries is largely explained by differences in countries' endowments and only to a minor extent by German banks' different treatment of these country groups. This is demonstrated by applying a decomposition technique to an augmented gravity model that is estimated for German foreign lending using a new micro panel data-set on individual claims from the Deutsche Bundesbank covering the period from 1996 to 2002.
Keywords: G21; F34; F30; 330; German bank lending; gravity models; Oaxaca decomposition analysis; Internationale Kreditvergabe; Deutsch; Kreditgeschäft; Schätzung; Vergleich; Industriestaaten; Entwicklungsländer